Ventilatory responses during experimental cycle-run transition in triathletes - Hue, O.; Le Gallais, D.; Boussana, A.; Collet, D.; Prefaut, Ch. (Medicine & Science in Sports & Exercise, 1999)
1) the C-R trial induced specific alterations in pulmonary function that may be associated with respiratory muscle fatigue and/or exercise-induced hypoxemia, and 2) the greater V(dot)E observed during the first minute of running after cycling was due to the specificity of cycling. This reinforces the necessity for triathletes to practice multi-trial training to stimulate the physiological responses experienced during the swim-cycle and the cycle-run transitions.